Chronobiology and Chronotherapy-Related Effects in Non-Traumatic Pain Presentations in the Emergency Department: A Retrospective Study - Akgöl, Jale; Özdinç, Şerife; Karakoca, Serra; Alkan, Bahar Karya; Baş, Melisa; Gündoğdu, Berke Üzeyir; Başaran, Orhan; Çetin, Ferit Suat; Akkuş, Esra; Tanrıkulu, Kaan; Kaya, Zeynep Beyza; Şahin, İsmail; et al. (The European Research Journal, 2026)
Objectives: Pain is one of the most frequent reasons for emergency department (ED) admissions, yet the chronobiological patterns of pain-related presentations remain insufficiently explored. This study aimed to retrospectively analyze the temporal and seasonal characteristics of non-traumatic pain-related ED visits, with a focus on daily and seasonal variations influenced by circadian rhythms. Methods: This retrospective, descriptive, cross-sectional study included adult patients (≥18 years) who presented to the Afyonkarahisar Health Sciences University Adult ED with non-traumatic pain between January 1, 2023, and December 31, 2023. Cases were identified based on ICD-10 codes for headache (R51, G43, G44), chest pain (R07.1–R07.4), abdominal pain (R10.0–R10.4), and musculoskeletal pain (M54, M79, M25). Demographic data, admission times, diagnostic procedures, treatment initiation, and hospitalization rates were analyzed. Statistical analyses utilized appropriate parametric and non-parametric tests, with significance set at P